The IRE1α pathway in glomerular diseases: The unfolded protein response and beyond - Navarro-Betancourt, José R.; Cybulsky, Andrey V. (Frontiers in Molecular Medicine, 2022)
Endoplasmic reticulum (ER) function is vital for protein homeostasis (“proteostasis”). Protein misfolding in the ER of podocytes (glomerular visceral epithelial cells) is an important contributor to the pathogenesis of human glomerular diseases. ER protein misfolding causes ER stress and activates a compensatory signaling network called the unfolded protein response (UPR). Disruption of the UPR, in particular deletion of the UPR transducer, inositol-requiring enzyme 1α (IRE1α) in mouse podocytes leads to podocyte injury and albuminuria in aging, and exacerbates injury in glomerulonephritis. The UPR may interact in a coordinated manner with autophagy to relieve protein misfolding and its consequences. Recent studies have identified novel downstream targets of IRE1α, which provide new mechanistic insights into proteostatic pathways. Novel pathways of IRE1α signaling involve reticulophagy, mitochondria, metabolism, vesicular trafficking, microRNAs, and others. Mechanism-based therapies for glomerulopathies are limited, and development of non-invasive ER stress biomarkers, as well as targeting ER stress with pharmacological compounds may represent a therapeutic opportunity for preventing or attenuating progression of chronic kidney disease.